Pengaruh Komitmen Organisasional Dan Disiplin Kerja Terhadap Kinerja Karya Wan Melalui Kepuasan Kerja Sebagai Variabel Intervening - M. Aditya Putra Pratama; Fareshti Nurdiana Dihan (Universitas Muhammadiyah Yogyakarta, 2017)
Organizational commitment, work discipline and job satisfaction to be part of the factors that influence performance. The purpose of this study was to determine the effect of organizational commitment and discipline on performance through job satisfaction as an intervening variable partially and simultaneously. This study also aimed to determine the effect of organizational commitment and discipline on performance through job satisfaction as an intervening variable directly and indirectly. This study was conducted to 150 respondents employees of PT. Arief Nirwana Utama. The research method used is quantitative method uses statistical and descriptive analysis.The results of this study are (1) there is a significant effect of organizational commitment on employee job satisfaction. (2) there is a significant impact on job satisfaction labor discipline employees. (3) there is a significant effect of organizational commitment and discipline of work simultaneously on employee job satisfaction. (4) there is a significant effect of organizational commitment on performance. (5) there is a significant influence on the performance of employees work discipline. (6) significant influence of organizational commitment and discipline of work simultaneously on employee performance. (6) significant influence of organizational commitment and discipline of work simultaneously on employee performance. (7) significant influence of job satisfaction on employee performance. (8) there is a significant indirect effect of organizational commitment on performance through employee satisfaction. (9) there is a significant indirect effect on the performance of work discipline through employee satisfaction.